Comprehensive analysis of systemic, metabolic, and molecular changes following prospective change to low-carbohydrate diet in adults with type 2 diabetes mellitus in India - Bhandarkar, Nikhil Suresh; Shetty, K. Bhujang; Shetty, Naren; Shetty, Keerthy; Kiran, Anupama; Pindipapanahalli, Narendra; Shetty, Rohit; Ghosh, Arkasubhra (Frontiers in Nutrition, 2024)
Purpose South Asians, especially Indians, face higher diabetes-related risks despite lower body mass index (BMI) compared with the White population. Limited research connects low-carbohydrate high-fat (LCHF)/ketogenic diets to metabolic changes in this group. Systematic studies are needed to assess the long-term effects of the diet, such as ocular health. Method In this prospective, observational study, 465 candidates aged 25–75 years with type 2 diabetes included with institutional ethics approval. A total of 119 subjects were included in the final study assessment based on the availability of pathophysiological reports, tears, and blood samples collected at baseline, 3rd, and 6th months. Serum and tear samples were analyzed by an enzyme-linked lectinsorbent assay, to examine secreted soluble protein biomarkers, such as IL-1β (interleukin 1 Beta), IL-6 (interleukin 6), IL-10 (interleukin 10), IL-17A (interleukin 17A), MMP-9 (matrix metalloproteinase 9), ICAM-1 (intercellular adhesion molecule 1), VEGF-A (vascular endothelial growth factor A), and TNF-α (tumor necrosis factor-alpha). A Wilcoxon test was performed for paired samples. Spearman’s correlation was applied to test the strength and direction of the association between tear biomarkers and HbA1c. p-value of < 0.05 was considered significant. Results After a 3- and 6-month LCHF intervention, fasting blood sugar decreased by 10% (Δ: −14 mg/dL; p < 0.0001) and 7% (Δ: −8 mg/dL; p < 0.0001), respectively. Glycated hemoglobin A1c levels decreased by 13% (Δ: −1%; p < 0.0001) and 9% (Δ: −0.6%; p < 0.0001). Triglycerides reduced by 22% (Δ: −27 mg/dL; p < 0.0001) and 14% (Δ: −19 mg/dL; p < 0.0001). Total cholesterol reduced by 5.4% (Δ: −10.5 mg/dL; p < 0.003) and 4% (Δ: −7 mg/dL; p < 0.03), while low-density lipoprotein decreased by 10% (Δ: −11.5 mg/dL; p < 0.003) and 9% (Δ: −11 mg/dL; p < 0.002). High-density lipoprotein increased by 11% (Δ: 5 mg/dL; p < 0.0001) and 17% (Δ: 8 mg/dL; p < 0.0001). At the first follow-up, tear proteins such as ICAM-1, IL-17A, and TNF-α decreased by 30% (Δ: −2,739 pg/mL; p < 0.01), 22% (Δ: −4.5 pg/mL; p < 0.02), and 34% (Δ: −0.9 pg/mL; p < 0.002), respectively. At the second follow-up, IL-1β and TNF-α reduced by 41% (Δ: −2.4 pg/mL; p < 0.05) and 34% (Δ: −0.67 pg/mL; p < 0.02). Spearman’s correlation between HbA1c and tear analytes was not statistically significant. Conclusion The LCHF diet reduces the risk of hyperglycemia and dyslipidemia. Changes in tear fluid protein profiles were observed, but identifying promising candidate biomarkers requires validation in a larger cohort.